# math

posted by .

I am suppose to simplify the following problems:

sqrt(x)/x
e^(1+lnx)
(I have no clue.)
ln(1/2)
(I know this problem translates--> e^x=1/2--> but how would you solve it w/o a calculator?)
e^(3lnx)
([e^(lnx^3)]--> is it equal to 3?)

sqrt(x)/x

I agree with you.
you could do this: x^(1/2)/x
= x(-1/2)
= 1/√x but that is certainly not simpler.

e^(1+lnx)
(I have no clue.)

e^(1+lnx)
=(e)(e^lnx)
=e(x) = ex

n(1/2)
(I know this problem translates--> e^x=1/2--> but how would you solve it w/o a calculator?)

ln(1/2)
= ln 1 - ln 2
= 0 - ln 2
= -ln 2

e^(3lnx)
([e^(lnx^3)]--> is it equal to 3?)

yes, based on the fact that a^(loga k = k

## Similar Questions

1. ### math

how would you solve for y in this problem: ln(y-1)-ln2 = x +lnx ln(y-1)-ln2 = x +lnx Solve for y... ln[(y-1)/2]]=x + lnx take the antilog of each side (y-1)/2= e^(x+lnx) solve for y.
2. ### Logarithms

lnx^5 - lnx^2 = 3 solve for the unknowns as a list. I tried using my calculator but apparently my answer is opposite ends of the universe
3. ### Math

I cant figure this question out. I could use some help. Solve for x lnx-lnx^2+ln5 = 0 Simplify the answer
4. ### L'Hopital's rule

Find lim x->1+ of [(1/(x-1))-(1/lnx)]. Here is my work... =(lnx-(x-1)) / ((x-1)(lnx)) =(lnx-1) / (lnx+ (x+1)/x) This becomes(1/x) / ((1/x)+(1/x^2)) which becomes 1/ (1/x^2) This equals 1/2. I understand the answer has to be -1/2, …
5. ### Calculus 1

Find the derivative of y with respect to x. y=(x^6/6)(lnx)-(x^6/36) So far this is what I've gotten: y=(x^6/6)(lnx)-(x^6/36) y=(1/6)x^6(lnx)-(1/36)x^6 y'=(1/6)x^5(1/x)+lnx(x^5)-(1/6)x^5 What do I do now?
6. ### calculus

sorry to ask a second question so soon, but i'm just not getting this one. if f(x)= 3x lnx, then f'(x)=?
7. ### Calculus

Find the derivatives, dy/dx for the following functions. a. x^2y^4 = lnx + 3y b. y = ln(2x^2 + 1) c. y = ln(ãx) d. y = lnx/x e. y = x^2 lnx f. y ß log_2⁡(3x)
8. ### Calculus

what is the limit as h approaches 0 of ((x+h)^pi-x^pi)/h?
9. ### math: pre-calculus

Let u=ln and v=ln y. Write the expression ln(5√(x3√y)) in terms of u and v. for example, lnx^3y = lnx^3+lny = 3lnx+lny = 3u+v
10. ### math: pre-calculus

Let u=lnx and v=lny. Write the expression ln3√x/2y in terms of u and v. For example, lnx^3y=lnx^3+lny=3lnx +lny= 3u+v.

More Similar Questions